2021
DOI: 10.3390/life11020151
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Acinetobacter baumannii Genetic Characterization and Spread in Lithuania in 2014, 2016, and 2018

Abstract: Bacterial resistance to antimicrobial agents plays an important role in the treatment of bacterial infections in healthcare institutions. The spread of multidrug-resistant bacteria can occur during inter- and intra-hospital transmissions among patients and hospital personnel. For this reason, more studies must be conducted to understand how resistance occurs in bacteria and how it moves between hospitals by comparing data from different years and looking out for any patterns that might emerge. Multidrug-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The number of cases of bacterial nosocomial infections resistant to antimicrobial agents has increased worldwide over the last decade [ 4 ]. A. baumannii is considered one of the most important causes of antimicrobial resistance in health care facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of cases of bacterial nosocomial infections resistant to antimicrobial agents has increased worldwide over the last decade [ 4 ]. A. baumannii is considered one of the most important causes of antimicrobial resistance in health care facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A. baumannii is considered one of the most important causes of antimicrobial resistance in health care facilities. A. baumannii strains cause outbreaks around the world due to their remarkable ability to adapt to the changes in the environment and to acquire different resistance mechanisms against multiple antimicrobials [ 4 ]. This study aimed to determine the types of β -lactamases and their combinations produced by MDR A. baumannii strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in Lithuania, it was found that there is no relationship between the specific years in which the study was conducted and the clustering of the isolates. On the other hand, it was found that most varieties belonged to Abaum_0845 and Abaum_0826 (Kirtikliene et al, 2021). A study conducted by Peerayeh et al showed that different strains are circulating in two Iranian hospitals and the population of XDR A. baumannii in Iranian hospitals is genetically diverse, which necessitates preventive measures and strict control (Najar Peerayeh and Karmostaji, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This study further highlighted the circulation of several AMR genes and the genetic relatedness among various A. baumannii isolates. 72 Notably, according to a PubMed search, there is no available study from India on MLVA-based molecular typing of A. baumannii . However, the molecular epidemiology of 73 CRAB isolates from tertiary care hospitals in Java and Sulawesi islands, Indonesia, was recently determined using MLVA.…”
Section: Multilocus Variable-number Tandem-repeat (Mlva)mentioning
confidence: 99%